Sistem Informasi Pelayanan Pengaduan Masyarakat pada Dinas Pekerjaan Umum DDN Penataan Ruang Batang - Widya Nurul Pranestiana; Aya Sophia; Andy Arif (Pusat Riset dan Inovasi Nasional, 2023)
The Public Works and Spatial Planning Office of Batang Regency is a government agency that deals whit the construction and repair of public facilities in Batang Regency. The public works and spatial planning office is located at Jl. Jend. Sudirman No. 272 Batang Regency. Currently, the public complaint process in the DPUPR in the spatial planning sector has not been going well and has several problems including the complaint service process not using Social Media, but still using letters, so the delivery process tends to take a long time. In addition, the process of distributing reports using letters causes inconsistencies in data, the procedures currently being implemented require a long time for complaints to be responded to, resulting in inefficient time and costs. Therefore, in making this thesis a Public Complaint Service Information System will be designed at the Public Works and Batang Spatial Planning Office. This system uses the Waterfall development method, and uses white box, black box and uat testing methods. From the results of this study, it is hoped that it can help the community to make the complaint process easier.